Dyslexia in higher education – teacher’s perspective: scoping review - Černickaja, Karin; Sokolová, Lenka (Frontiers in Education, 2024)
The experience of dyslexic students is influenced by the beliefs, knowledge, attitudes, and practices of their teachers at all levels of education, including the university. The purpose of this review is to explore the empirical knowledge of dyslexic university students from the point of view of their teachers. Following the PRISMA guidelines, 12 studies (out of the 771 retrieved from 5 main relevant databases) met the inclusion criteria. Reflexive thematic analysis was used to analyse the included studies. Three main themes were identified: dyslexia = grey area; "inclusive university"; and practical training is necessary. In conclusion, awareness of dyslexia among university teachers is sufficient, and their attitudes towards dyslexic students are mostly positive, while expressing some concerns, which would deserve closer examination directly in practice. Higher education teachers would appreciate practical training to acquire skills to work with students with dyslexia. These trainings have the potential to increase the self-efficacy of teachers and thus overall support the wellbeing not only of teachers but also of dyslexic students. This study advances the existing literature on dyslexia in higher education by adding the point of view of higher education teachers. Based on the results of this study, it is clear that universities should provide more support to their teaching staff, including guidance and practical training, so that their courses could become inclusive and welcoming for all students (including students with dyslexia).